1998
DOI: 10.1177/002580249803800210
|View full text |Cite
|
Sign up to set email alerts
|

Return to Special: An Examination of the Characteristics of Patients Who Returned to Ashworth Special Hospital

Abstract: Sixteen patients were returned to Ashworth in a one-year period (five second admissions, 10 failed leave of absence and one warrant of recall) making up 31% of admissions for the year. Demographic details and reasons for return were collected. Fifty per cent of patients had a clinical diagnosis of personality disorder. Reasons for return included relapse of psychosis, persistent transgression of boundaries, aggression or threatened aggression, unsuitable placements and failure to progress towards discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Similar reasons for patients' failures at medium secure units have also been reported previously in studies comprising other samples of patients from high secure services (e.g., Cope & Ward, 1993;Tavernor, Swinton, Collins, Brook, & Beadle, 1998). Importantly, Skelly (1994aSkelly ( , 1994b has suggested that patients' disengagement from treatment at medium secure units and their active transgression of boundaries results from the stresses of the transfer, including the removal of former privileges and the effects of a 'special hospital' label.…”
Section: Discussionsupporting
confidence: 68%
“…Similar reasons for patients' failures at medium secure units have also been reported previously in studies comprising other samples of patients from high secure services (e.g., Cope & Ward, 1993;Tavernor, Swinton, Collins, Brook, & Beadle, 1998). Importantly, Skelly (1994aSkelly ( , 1994b has suggested that patients' disengagement from treatment at medium secure units and their active transgression of boundaries results from the stresses of the transfer, including the removal of former privileges and the effects of a 'special hospital' label.…”
Section: Discussionsupporting
confidence: 68%
“…The cost difference between high‐security and medium‐security hospital beds (Centre for Mental Health, ) is an important consideration, but, above all, clinicians are concerned that delay may cause frustration, which if left unresolved, may jeopardise onward cooperation with treatment. Skelly () reported reasons for recall to high security which included disengagement from treatment (Cope and Ward, ; Tavernor et al, ; Tetley et al, ).…”
Section: Introductionmentioning
confidence: 99%